Differential Responses of Wheat (Triticum aestivum L.) and Cotton (Gossypium hirsutum L.) to Nitrogen Deficiency in the Root Morpho-Physiological Characteristics and Potential MicroRNA-Mediated Mechanisms - Xue, Huiyun; Liu, Jia; Oo, Sando; Patterson, Caitlin; Liu, Wanying; Li, Qian; Wang, Guo; Li, Lijie; Zhang, Zhiyong; Pan, Xiaoping; Zhang, Baohong (Frontiers in Plant Science, 2022)
Understanding the mechanism of crop response to nitrogen (N) deficiency is very important for developing sustainable agriculture. In addition, it is unclear if the microRNA-mediated mechanism related to root growth complies with a common mechanism in monocots and dicots under N deficiency. Therefore, the root morpho-physiological characteristics and microRNA-mediated mechanisms were studied under N deficiency in wheat (Triticum aestivum L.) and cotton (Gossypium hirsutum L.). For both crops, shoot dry weight, plant dry weight and total leaf area as well as some physiological traits, i.e., the oxygen consuming rate in leaf and root, the performance index based on light energy absorption were significantly decreased after 8 days of N deficiency. Although N deficiency did not significantly impact the root biomass, an obvious change on the root morphological traits was observed in both wheat and cotton. After 8 days of treatment with N deficiency, the total root length, root surface area, root volume of both crops showed an opposite trend with significantly decreasing in wheat but significantly increasing in cotton, while the lateral root density was significantly increased in wheat but significantly decreased in cotton. At the same time, the seminal root length in wheat and the primary root length in cotton were increased after 8 days of N deficiency treatment. Additionally, the two crops had different root regulatory mechanisms of microRNAs (miRNAs) to N deficiency. In wheat, the expressions of miR167, miR319, miR390, miR827, miR847, and miR165/166 were induced by N treatment; these miRNAs inhibited the total root growth but promoted the seminal roots growth and lateral root formation to tolerate N deficiency. In cotton, the expressions of miR156, miR167, miR171, miR172, miR390, miR396 were induced and the expressions of miR162 and miR393 were inhibited; which contributed to increasing in the total root length and primary root growth and to decreasing in the lateral root formation to adapt the N deficiency. In conclusion, N deficiency significantly affected the morpho-physiological characteristics of roots that were regulated by miRNAs, but the miRNA-mediated mechanisms were different in wheat and cotton.